Lateral Cephalometric Analysis of Nasal Morphology in Patients Visiting Nishtar Institute of Dentistry: Lateral Cephalometric Analysis of Nasal Morphology - Jamshed , Sameera; Zubair Hassan Awaisi; Ahmed, Zubair (Pakistan Journal of Health Sciences, 2023)
Nasal morphology is the keystone of facial aesthetics. Being the most prominent part of the face, the shape and position of the nose greatly influence the facial profile and nasal soft tissue thickness also plays a vital role in orthodontic diagnosis and treatment planning. Objective: To evaluate the soft tissue nasal morphology in individuals presenting with different skeletal patterns such as skeletal class 1 and skeletal class 2 jaw relationship. Methods: It was Comparative Cross-sectional study conducted in Orthodontics Department of Nishtar Institute of Dentistry for the period of six months (5th Mar 2020 to 6th Jun 2021). Study sample consisted of Lateral cephalometric radiographs of 65 subjects. Age range of sampled subjects was 19-26 years (mean age 20.93). The sample was divided into two groups on basis of the Skeletal jaw relationship as class-1 and class-2. An Independent t-test was applied for evaluation of the difference in lateral nasal morphology between both groups. Results: Notable differences were found between skeletal class 1 and skeletal class 2 groups for the prominence of the mandible and Linear distance between soft tissue Pogonion and Pronasale. Considerable differences in measurements of nasal depth, nasofrontal angle, nasal tip projection angle, nasofacial angle and nasomental angle were found. Conclusions: It is concluded that nasal morphology was greatly influenced by not only the underlying skeletal jaw relationship yet other factors e.g., dentition along with soft tissue thickness were also responsible for nasal morphology differences among various skeletal patterns. Gender dimorphism also exists for various nasal features.